Association of circulating retroviral gp70-anti-gp70 immune complexes with murine systemic lupus erythematosus (The Rockefeller University Press, 1979)
Endogenous retroviral gp70 was investigated as a participant in the pathogenesis of a lupus-like disease that spontaneously develops in four kinds of mice (NZB, NZB x W MRL/1, and male BXSB). Sera from these strains contain a heavy form of gp 70 that varies in sedimentation rates from 9S to 19S in sucrose density gradient analysis and appears with the onset of disease and persists throughout its course. Immunologically normal strains of mice do not develop rapidly sedimenting gp70 by 8-10 mo of life. The fact that the heavy gp70 is selectively absorbed with anti-IgG antibodies or with Staphylococcus aureus protein A suggests that it is complexed with antibodies. The incidence and quantities of these gp70 ICs rise with the progression of disease in all strains with lupus. These findings suggest that Ig- complexed heavy gp70 may be involved in the pathogenesis of glomerulonephritis of mice with SLE.